2022
DOI: 10.1177/18632521221106383
|View full text |Cite
|
Sign up to set email alerts
|

The modified Kocher criteria for septic hip: Does it apply to the knee?

Abstract: Background: Pediatric septic arthritis is a surgical emergency and timely diagnosis prevents serious complications. To differentiate between septic hip and transient synovitis, the predictive value of four original Kocher criteria (fever, inability to bear weight, elevated serum white blood cell count, and elevated erythrocyte sedimentation rate) plus Caird’s addition of elevated C-reactive protein have been studied, termed the modified Kocher criteria. These criteria have not been tested extensively on septic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…One study, for instance, reported that CRP and ESR were predictive for septic hip arthritis compared to transient synovitis but that they were not predictive for septic knee arthritis. 25 Limited performance of the KC in children with K. kingae septic hip arthritis was also reported by Yagupsky et al 22 Unexpectedly, the scores of both clinical prediction rules did not differ between K. kingae and S. aureus infections, or other microbiologically confirmed infections. However, we might be limited to detect small differences between pathogen groups, due to our sample size.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…One study, for instance, reported that CRP and ESR were predictive for septic hip arthritis compared to transient synovitis but that they were not predictive for septic knee arthritis. 25 Limited performance of the KC in children with K. kingae septic hip arthritis was also reported by Yagupsky et al 22 Unexpectedly, the scores of both clinical prediction rules did not differ between K. kingae and S. aureus infections, or other microbiologically confirmed infections. However, we might be limited to detect small differences between pathogen groups, due to our sample size.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, children with K. kingae hip arthritis could have more invasive disease leading to a more severe presentation compared to the presentation in K. kingae knee arthritis. One study, for instance, reported that CRP and ESR were predictive for septic hip arthritis compared to transient synovitis but that they were not predictive for septic knee arthritis 25 …”
Section: Discussionmentioning
confidence: 99%
“…Despite its limitations, this retrospective study is one of the few studies concentrated on the knee joint effusion of pediatric patients and the potential distinguishing parameters between septic and non-septic arthritis [ 26 , 27 , 28 , 29 ]. Kocher predictive criteria for the hip joint are not applicable for the prediction of septic knee arthritis [ 26 ], and neither is the modified Kocher–Caird [ 2 , 30 ]. However, in recent studies, the combination of two specific factors (the inability to bear weight and an elevated C-reactive protein) was found to be strongly predictive [ 2 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kocher predictive criteria for the hip joint are not applicable for the prediction of septic knee arthritis [ 26 ], and neither is the modified Kocher–Caird [ 2 , 30 ]. However, in recent studies, the combination of two specific factors (the inability to bear weight and an elevated C-reactive protein) was found to be strongly predictive [ 2 , 30 ]. As an alternative to the original Kocher criteria, Baldwin et al found that by increasing the number of criteria they achieved higher predictive values which included: pain with an arc of motion below 30 degrees, CRP level >4.0 mg/L, notion of episodes of fever, and an age below 2 years were all positive predictive values which were able to help distinguish septic arthritis of the knee from non-septic forms such as Lyme arthritis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of CRP of >20 mg/L (modified Kocher’s criteria), with the other four features, was independently found to have a 98% positive predictive value 5. It has also been shown that the presence of high CRP (>40) and inability to weight bear with a sore knee had an 89.7% positive predictive value for a septic knee over other diagnoses 6…”
Section: Case: Partmentioning
confidence: 96%